2010
DOI: 10.3109/10428191003706947
|View full text |Cite
|
Sign up to set email alerts
|

Large granular lymphocyte leukemia: natural history and response to treatment

Abstract: Large granular lymphocyte leukemia (T-LGL) is an indolent T lymphoproliferative disorder that was difficult to diagnose with certainty until clonality testing of the T cell receptor gene became routinely available. We studied the natural history and response to treatment in 25 consecutive patients with T-LGL diagnosed between 2004 and 2008 in which the diagnosis was confirmed by molecular analysis, to define an effective treatment algorithm. The median age at diagnosis was 61 years (range 27-78), with a male t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
0
23
0
2
Order By: Relevance
“…These results were confirmed in further series, and MTX has been mainly proposed as first-line therapy. 59,65,69 In a larger series of 62 patients, we recently demonstrated that the 55% overall response rate was slightly lower than that reported in the limited series and that a significant proportion of patients relapsed on therapy. Indeed, 12 of 18 patients (67%) followed more than one year relapsed, raising the question of the long-term efficacy of such treatment.…”
Section: Mtxmentioning
confidence: 89%
See 2 more Smart Citations
“…These results were confirmed in further series, and MTX has been mainly proposed as first-line therapy. 59,65,69 In a larger series of 62 patients, we recently demonstrated that the 55% overall response rate was slightly lower than that reported in the limited series and that a significant proportion of patients relapsed on therapy. Indeed, 12 of 18 patients (67%) followed more than one year relapsed, raising the question of the long-term efficacy of such treatment.…”
Section: Mtxmentioning
confidence: 89%
“…12,65,69,[76][77][78][79][80][81][82] The overall ORR indicates overall response rate; CHR, complete hematologic response; -, not applicable; PRCA, pure red cell aplasia; and CR, complete response. *A total of 50-100 mg/day or 250-500 mg intravenously.…”
Section: Purine Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metotreksat (MTX, methotrexate) jest lekiem I linii w białaczce T-LGL; zalecana dawka to 5-10 mg/m² powierzchni ciała raz w tygodniu [41,69]. W badaniu Bareau i wsp.…”
Section: Leczenie Immunosupresyjneunclassified
“…Jednak większość autorów proponuje CsA jako II linię leczenia, ponieważ nie powoduje ona eradykacji komórek białaczkowych. Odsetek odpowiedzi jest bardzo różny w poszczególnych badaniach i nierzadko w trakcie terapii dochodzi do utraty odpowiedzi [20,40,41,69,[71][72][73].…”
Section: Leczenie Immunosupresyjneunclassified